2014
DOI: 10.1200/jco.2014.32.4_suppl.367
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib monotherapy in patients with inoperable/recurrent germ cell tumors (GCT) refractory to chemotherapy: Phase II study.

Abstract: 367 Background: The phase II trial was conducted in the population of incurable patients with refractory or relapsed GCT to evaluate the activity of sorafenib, an oral multitarget inhibitor of Raf kinase and the tyrosine kinases VEGFR-2 and PDGFR-alpha. Methods: Patients with progressive metastatic GCT received sorafenib monotherapy continuosly 400mg bid until progression of disease or unacceptable toxicity. Serum tumor markers (STM) were assessed every 4 weeks and imaging was performed every 12 weeks. Respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, clinical results were rather disappointing, since sunitinib was the only agent to achieve short-lived partial remissions in 13% of 33 patients and was well tolerated in a phase II trial [20], but a second trial failed to confirm these results [21]. Pazopanib and sorafenib only induced tumor marker declines in 80% and 44% of patients in small phase II trials without any objective responses, but 33% of patients achieved progression-free survival of at least 3 months with pazopanib, and 17% of sorafenib-treated patients achieved disease stabilization for more than 12 months [22,23].…”
Section: Growth Factor Receptors/receptor Tyrosine Kinases and Ligandsmentioning
confidence: 93%
“…However, clinical results were rather disappointing, since sunitinib was the only agent to achieve short-lived partial remissions in 13% of 33 patients and was well tolerated in a phase II trial [20], but a second trial failed to confirm these results [21]. Pazopanib and sorafenib only induced tumor marker declines in 80% and 44% of patients in small phase II trials without any objective responses, but 33% of patients achieved progression-free survival of at least 3 months with pazopanib, and 17% of sorafenib-treated patients achieved disease stabilization for more than 12 months [22,23].…”
Section: Growth Factor Receptors/receptor Tyrosine Kinases and Ligandsmentioning
confidence: 93%
“…Brentuximab vedotin is an antibody-drug conjugate approved in Hodgkin lymphomas and systemic anaplastic large cell lymphoma targeting the CD30. This antigen is regularly expressed in embryonal carcinoma; when tested in salvage treatment of CD-30 positive germ cell tumors, the RR was 22.2 % with 6-month OS of 85.7 % [76]. Another phase II associating bevacizumab combined with high-dose chemotherapy with autologous stem-cell transplant demonstrated an OS of 58.1 % with a follow-up of 46 months [77].…”
Section: Clinical Trials Using Targeted Therapies In Relapsed or Refrmentioning
confidence: 96%
“…At the ASCO annual meeting 2014, two abstracts were presented evaluating antiangiogenic TKI, pazopanib and sorafenib in chemo-resistant, heavily treated germ cell tumors. Pazopanib is endowed with preliminary activity [75], while Sorafenib did not present significant activity in patients despite some prolonged stable diseases [76]. Another abstract in ASCO 2014 evaluated Alvocidib/Flavopiridol, a CDK9 inhibitor, in combination with oxaliplatin with or without fluorouracil and leucovorin calcium in a phase II trial that showed an RR of 24 % in Alvocidib/FOLFOX arm and a PFS of 2.3 months and a OS of 7.3 months [74].…”
Section: Clinical Trials Using Targeted Therapies In Relapsed or Refrmentioning
confidence: 98%
“…However, those treatments fail about 15%-20% of patients, a subgroup that is thus in need of additional treatment options. Recent trials using targeted therapies in such patients have yielded disappointing results [38][39][40][41] . Although gcts have been shown to express PD-L1 42 , and a number of case studies and series have described activity for cpis in those tumours [43][44][45] , early-phase trials have been disappointing to date.…”
Section: Testicular Germ-cell Tumoursmentioning
confidence: 99%